Visual outcomes of combined cataract surgery and minimally invasive glaucoma surgery. Issue 10 (October 2020) - Sarkisian, Steven R.; Radcliffe, Nathan; Harasymowycz, Paul; Vold, Steven; Patrianakos, Thomas; Zhang, Amy; Herndon, Leon; Brubaker, Jacob; Moster, Marlene; Francis, Brian
Abstract : A comprehensive review of MIGS procedures currently combined with cataract surgery with a focus on visual outcomes based on the literature and the experience of the ASCRS Glaucoma Clinical Committee. Abstract : Minimally invasive glaucoma surgery (MIGS) has become a reliable standard of care for the treatment of glaucoma when combined with cataract surgery. This review describes the MIGS procedures currently combined with and without cataract surgery with a focus on visual outcomes based on the literature and the experience of the ASCRS Glaucoma Clinical Committee.